The bond market in Indonesia an ASEAN+3 bond market guide update. ([Manila] Asian Development Bank, 2021)
This publication provides updates on the bond market in Indonesia since 2017.
Overview - - Legal and Regulatory Framework - - Legal and Regulatory Framework - - Bond and Note Transactions and Trading Market Infrastructure - - Bond Market Costs and Taxation - - Market Size and Statistics - - The Indonesian Islamic Bond Market - - Recent Developments and Future Direction - - Appendixes.
Keywords: Financial institutions -- Indonesia; Money markets -- Indonesia; Electronic books